A–D–A-type S, N-heteropentacene-based hole transport materials for dopant-free perovskite solar cells1. Issue 34 (14th September 2015) - Steck, Christopher; Franckevičius, Marius; Zakeeruddin, Shaik Mohammed; Mishra, Amaresh; Bäuerle, Peter; Grätzel, Michael
<x xml:space="preserve">Abstract</x> Heteropentacene-based A–D–A type hole transport materials with suitable frontier orbital energy levels were synthesized and used in perovskite solar cells showing power conversion efficiencies up to 11.4%.